2004
DOI: 10.1002/j.2164-490x.2004.tb00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Counsel from a Former Editor and the Current Editor: Successful Research and Writing for Publication in The Journal of Humanistic Counseling, Education and Development

Abstract: A former editor (A. S. McGowan) of The Journal of Humanistic Counseling, Education and Development, currently the editor of the Journal of Counseling & Development, and the current editor (M. B. Scholl) present strategies and guidelines for prospective authors to enhance the chance of successful publication in this and other American Counseling Association‐refereed journals. This article is an updated version of one that was written by A. S. McGowan and that appeared in 1997 in the Journal of Humanistic Educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Although Hansen () supported the assertion that qualitative research should be a standard methodology for humanistic counseling research through references to seminal theorists/researchers consistent with the onset of the humanistic counseling movement (e.g., Maslow, ; Matson, ; Rogers, ), The Journal of Humanistic Counseling has had a long history of recognizing quantitative research as a pertinent component to humanistic counseling research. McGowan and Scholl () referenced the American Counseling Association Publications Committee in their statement related to the equality of quantitative and qualitative research for publishing in The Journal of Humanistic Counseling, Education and Development . Scholl () emphasized a need for humanistic counseling research to encompass humanistic themes, while not identifying a preference to any particular research methodology.…”
Section: Views Of Humanistic Counseling Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Hansen () supported the assertion that qualitative research should be a standard methodology for humanistic counseling research through references to seminal theorists/researchers consistent with the onset of the humanistic counseling movement (e.g., Maslow, ; Matson, ; Rogers, ), The Journal of Humanistic Counseling has had a long history of recognizing quantitative research as a pertinent component to humanistic counseling research. McGowan and Scholl () referenced the American Counseling Association Publications Committee in their statement related to the equality of quantitative and qualitative research for publishing in The Journal of Humanistic Counseling, Education and Development . Scholl () emphasized a need for humanistic counseling research to encompass humanistic themes, while not identifying a preference to any particular research methodology.…”
Section: Views Of Humanistic Counseling Researchmentioning
confidence: 99%
“…The status and typology of counseling research is a recurring topic in a variety of specialty areas in counseling, and humanistic counseling in particular (e.g., Dollarhide, ; Erford, Erford, & Broglie, ; Hansen, ; Lemberger, ; McGowan & Scholl, ; Minor & Minor, ; Rogers, ; Scholl, ; Wilks & Ratheal, ). However, the manner in which research from a humanistic perspective, hereinafter referred to as humanistic counseling research, may be conducted is under debate.…”
mentioning
confidence: 99%
“…In most cases, it is best to use only the most current references (less than 10 years old) and landmark "older" articles and writings (e.g., a theorist's seminal publication). McGowan and Scholl (2004) suggested that most cited references be published within the prior 5 years. Additionally, writers should reference rigorous academic journals (peer-reviewed) and avoid heavy reliance on the popular press and textbooks.…”
Section: Appropriate Citationmentioning
confidence: 99%
“…Often, the References section of student papers and manuscripts submitted for publication has inaccuracies (K. Hughey, personal communication, December 8, 2004;McGowan & Scholl, 2004). In the References, the writer should provide references for all sources cited in the paper.…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation